2023
DOI: 10.1186/s12884-023-05403-0
|View full text |Cite
|
Sign up to set email alerts
|

Short birth interval and its predictors among reproductive age women in high fertility countries in sub-Saharan Africa: a multilevel analysis of recent Demographic and Health Surveys

Abstract: Background In developing countries, short birth interval is one of the major public health issues. It is one of the leading cause’s adverse birth outcomes in the worldwide. Despite the fact that ending maternal and perinatal morbidity and mortality is one of the Sustainable Development Goals (SDG), the burden of the problem continues to be a huge concern in developing countries, including high fertility countries. Thus, this study aimed to determine the short birth interval and its predictors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 53 publications
6
13
2
Order By: Relevance
“…The ndings this study were found to be in line with the study conducted in Northwest Ethiopia (12). However, it was lower than the study conducted in Uganda(52.4%), Tanzania (48.4%), rural India (50%), Sub-Saharan Africa (58.7%), and other places of Ethiopia (62.9%) (2,(13)(14)(15)(16)). On the other hand, this nding is higher than studies conducted in Northern Ethiopia(23.3%,) and Bangladesh (26% ) respectively (4,17).…”
Section: Discussionsupporting
confidence: 83%
“…The ndings this study were found to be in line with the study conducted in Northwest Ethiopia (12). However, it was lower than the study conducted in Uganda(52.4%), Tanzania (48.4%), rural India (50%), Sub-Saharan Africa (58.7%), and other places of Ethiopia (62.9%) (2,(13)(14)(15)(16)). On the other hand, this nding is higher than studies conducted in Northern Ethiopia(23.3%,) and Bangladesh (26% ) respectively (4,17).…”
Section: Discussionsupporting
confidence: 83%
“…African countries with high fertility [23]. Another study in 35 sub-Saharan African countries found a pooled prevalence of 43.91%, with South Africa having the lowest prevalence (23.25%) and Chad having the highest (59.28%).…”
Section: Discussionmentioning
confidence: 98%
“…This high prevalence is common in many African countries. It has also been noted in the literature, ranging from 16.99% to 58.74%: analyses carried out on Demographic and Health Survey (DHS) databases showed that the pooled prevalence was 16.99% for 12 East African countries in a study published in 2023 [10], and 58.74% as a pooled prevalence in 10 African countries with high fertility [23]. Another study in 35 sub-Saharan African countries found a pooled prevalence of 43.91%, with South Africa having the lowest prevalence (23.25%) and Chad having the highest (59.28%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, including Ethiopia, many women still experience untimely and closely spaced pregnancies, despite the availability of family planning services. This situation exposes them to a higher risk of health issues and even death during pregnancy and childbirth (14,16,17). Efforts by the government and other stakeholders have not fully addressed this concern, as suboptimal or short birth intervals continue to occur (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%